Anthropos Redux: A Defence of Monism in the Anthropocene Epoch - Braidotti, Rosi (FRAME, Journal of Literary Studies, 2026)
This essay starts from the assumption that the historical situation of today is unprecedented in ecological, economic, sociopolitical, as well as affective terms. The era known as the Anthropocene requires new ways of thinking in order to account for new practices and discourses related to this situation. By offering a defence of Spinozist monism, this essay attempts to strike a critical balance between new and internally contradictory contemporary concerns, such as the fast technological developments on the one hand and the perpetuation of more familiar patterns of oppression, like structural economic inequalities, on the other. Both aspects of the present predicament will receive critical attention in the cartography of the Anthropocenic era that I will discuss here and which I read in terms of the posthuman condition.